Bleeding hepatico-cutaneous fistula – an unusual complication of the percutaneous liver biopsy - Mitrović Miroslav; Jovanović Milan; Bezmarević Mihailo; Milev Boško; Mirković Darko (Vojnosanitetski Pregled)
Introduction. An arteriovenous fistula is one of the complications that can occur during percutaneous liver biopsy (PLB). Hepatic arteriovenous fistula with chronic bleeding from the puncture site on the skin is an extremely rare complication following PLB. Case report. We present a 35-year-old woman with secondary anemia caused by chronic bleeding at the site of a granuloma caused by a previous liver biopsy performed 7 years ago. The patient was examined and treated for several years due to anemic syndrome. The pathological communication between the right hepatic vein, the anterior sectional branch of the portal vein, and the posterior arterial sectional branch were detected on a computed tomography scan and proven by fistulography. Due to the failed embolization, a laparotomy was performed, where a tumor mass was found in the VI and VII segment of the liver, which communicates with the skin. The tumor mass was removed by atypical resection of the VI and VII liver segments. Due to hemorrhage, reexploration was performed, where the bleeding was found from the surface of the resected liver parenchyma. The patient was released for home treatment two weeks after the last operation. Conclusion. Although PLB is a safe procedure, a complication in the form of bleeding sometimes occurs but with spontaneous cessation. In the presented patient, there was a complicated intra-hepatic arteriovenous-portal fistula with the formation of communication with the puncture site on the skin. That is the first published case of complications of this type after PLB.